The Effect of Government Development Expenditures on Unemployment Rate in the Provinces - Rahmat, Dear Mahnaz; Saeidi, Khalil (International Journal of Economics and Financial Issues, 2017)
The most important and significant way of creating employment and reducing the unemployment rate is through government policies, dependent on government development expenditures and the government are trying not only to provide the growth and development substrates of the country but also become effective in reducing the unemployment rate. The main question of this article is that "Do the government development expenditures can cause to reducing unemployment rates in different provinces? The present study in term of purpose is applied and in term of nature is causal-correlational with the type of the mixed data Research. The study period is 1998-2013. That in this period all provinces of the country with segregation in two provinces are divided into large and small provinces that are considered as a research population and statistics and relevant information have been obtained from sources of information and the Statistical Center of Iran. In order to analysis data and the estimation of econometrics patterns Excel and Eviews econometric software are used. The results revealed that Government development expenditures have a significant negative effect on the unemployment rate in the province. Also, all logarithmic models on large and small provinces for the government development expenditures on large provinces a negative coefficient 0.049 is obtained which is significant at 5% probability level and in small provinces negative coefficient of 0.07 is obtained which is significant at 5% probability level. So, the results relate to all algorithms models in large and small provinces showed that that the effect of government development expenditure in small provinces is more than the large provinces. Keywords: employment, unemployment, government development expenditures, panel data JEL Classifications: E24, J64